Wisconsin 4-H/Youth Development staff perspectives on Hispanic 4-H programs - O'Brien, Candis (My University, 2012)
The Hispanic population in Wisconsin is continuing to increase, with each of the 72 counties having Hispanic residents. As this population continues to increase, Extension and 4-H need to find ways to better meet the needs of Hispanic community members. The purpose of this study was to identify the perspectives of Wisconsin 4 H/Youth Development agents and staff on Hispanic 4-H programming. In particular, this study sought to find out what types of Hispanic 4-H programming are currently in existence in Wisconsin, whether or not Hispanic 4-H programming is seen as a necessity, and what Wisconsin 4-H/Youth Development agents and staff see as the major benefits and challenges of offering 4-H programming to the Hispanic population. This research was conducted through the use of a survey that was developed using the online survey tool, Qualtrics. In total, 84 Wisconsin 4-H/Youth Development agents and staff were sent an email invitation to participate in this survey. The survey consisted of both closed and open-ended questions and also included a 17 item five point Likert-type scale. The questions in the survey sought to determine background information, such as county Hispanic population and 4-H enrollment, as well as to find out information about existing programs and the perspectives of Wisconsin 4-H/Youth Development agents and staff. Results of this research indicated that only a few of the counties in Wisconsin currently offer some type of 4-H programming for the Hispanic population, although every county has Hispanic residents. The Wisconsin 4-H/Youth Development agents and staff surveyed indicated that increased programming for underrepresented audiences and programming that increased cultural awareness were of importance. This research also shows that additional research in the area of Hispanic 4-H programming needs to be conducted to determine how to better meet the needs of the Wisconsin 4-H/Youth Development agents and staff who plan and develop these types of programs.
Thesis (M.S.)--University of Wisconsin-River Falls, 2012. viii, 93 leaves. Includes bibliographical references (leaves 61-63).
Keywords: 4-H clubs--Wisconsin; 4-H Youth Development; Hispanic American youth--Wisconsin; 4-H clubs; 4-H; Hispanic population